Manajemen risiko reputasi pada perbankan syariah: Studi literature review - Mayasari, Nur Aulia Keysha (Maliki Interdisciplinary Journal, 2024)
The future of banking institutions really depends on their ability to manage banking itself. Primarily with risk management that will arise in the process of carrying out activities in banking. In this case, the aim is to face various rapid changes that will occur in the future. Conditions that have the potential for banking risks that will occur must of course be addressed and handled as best as possible. Therefore, Islamic banking has risk management, one of which is reputation risk. Reputation risk in banking is an assumption or image that has been embedded in a customer and banking stakeholders. This reputation will give rise to good and bad perceptions by the public about the bank. Reputation is an invisible asset that should be owned by banking institutions. Because reputation is one of the keys to a bank's success in fulfilling the wishes of various stakeholders. This reputation risk usually arises because it is based on other risks. Such as liquidity risk, operational risk and credit risk. Therefore, it is necessary to understand other risks that are related to reputation risk. Risk management is a series of methods and steps used to identify, measure and control all risks that arise in a series of banking activities. This research analysis was carried out descriptively in the VOSviewer application through a literature review study.